1990
DOI: 10.1001/archotol.1990.01870080084021
|View full text |Cite
|
Sign up to set email alerts
|

Reversible Hearing Loss in a Patient With Cryptococcosis

Abstract: A 16-year-old girl had hearing loss, paroxysmal tremor, gait disorders, and psychiatric disturbances as the initial manifestations of a cryptococcal meningoencephalitis. Imaging demonstrated an obstructive hydrocephalus, and neuro-otological explorations showed a retrocochlear deafness and diffuse brainstem involvement. Emphasis is on the deafness, which rarely occurs as a presenting symptom in this condition, and on its dramatic improvement following antimycotic therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2002
2002
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 5 publications
0
3
0
Order By: Relevance
“…The nature of hearing loss can be fluctuating [1], the degree of loss varying from unilateral moderate to bilateral profound [1,4], and possibly reversible [7]. As illustrated in this case, the difficulty in arriving at an early diagnosis can result in the patient being treated for idiopathic sudden hearing loss with steroids which can potentially aggravate the unrecognized infection [4].…”
Section: Discussionmentioning
confidence: 99%
“…The nature of hearing loss can be fluctuating [1], the degree of loss varying from unilateral moderate to bilateral profound [1,4], and possibly reversible [7]. As illustrated in this case, the difficulty in arriving at an early diagnosis can result in the patient being treated for idiopathic sudden hearing loss with steroids which can potentially aggravate the unrecognized infection [4].…”
Section: Discussionmentioning
confidence: 99%
“…1,6,11 In a case series reported by Wang et al, three of seven survivors had shown improvement in hearing after a three-year follow-up period. Indeed, several authors have described varying degrees of recovery in patients with hearing loss post-cryptococcal meningitis.…”
Section: Discussionmentioning
confidence: 97%
“…However, no conclusive evidence may be used to predict the clinical course of the hearing loss, as patients have shown varying results according to the literature. Indeed, several authors have described varying degrees of recovery in patients with hearing loss post-cryptococcal meningitis 1 , 6 , 11 . In a case series reported by Wang et al ., three of seven survivors had shown improvement in hearing after a three-year follow-up period 6 .…”
Section: Discussionmentioning
confidence: 99%